The impact of retail stores' practices of marketing deception on consumer purchasing behavior (Economic studies journal, 2025)
This study aimed to identify the impact of retail stores' practices of marketing deception on the purchasing behavior of the Libyan consumer, and to reveal the differences in the respondents' responses regarding purchasing behavior, based on a number of variables (gender, age, educational level, social status, monthly income level, profession). The study used the descriptive analytical approach; To achieve its objectives, a questionnaire tool was developed. The size of the study community was (449525) elements, using the quota sampling method, and the sample size was (384) individuals. The data were analyzed using the Statistical Package for Social Sciences (SPSS). The results of the study showed that there is an impact of marketing deception practices on the purchasing behavior of the Libyan consumer. The results of the study also showed that there were no statistically significant differences in the respondents' responses regarding the purchasing behavior of the Libyan consumer attributed to gender, educational level, monthly income level, social status, age, while statistically significant differences were found attributed to the profession. In conclusion, the study recommended the need to enhance consumer awareness through awareness programs targeting consumers; To provide them with the necessary tools to identify and protect themselves from fraudulent practices. It also recommended the necessity of cooperation between all state agencies in regulating marketing practices in the Libyan market, to ensure the provision of a fair and transparent commercial environment that contributes to enhancing trust between consumers and retail stores.
Keywords: Marketing deception; purchasing behavior; retail stores; Libyan consumer